Shedding light on the impacts of gestational exposure to polystyrene nanoplastics on the reproductive performance of Poecilia reticulata female and on the biochemical response of embryos - Malafaia, Guilherme [UNESP] (2022)
Although the toxicity of nanoplastics (NPs) has already been reported in experimental aquatic models, their possible effects on the reproductive performance of viviparous freshwater fish and their consequences for embryos, so far, are unknown. Thus, we aimed to evaluate whether the gestational exposure of Poecilia reticulata to polystyrene NPs (PS NPs) impacts the reproductive performance of females, induces teratogenic effects and/or predictive alterations of redox unbalance and cholinesterasic effect. Our results demonstrate that gestational exposure of P. reticulata females (for 30 days) to PS NPs (50 µg/L) affected reproductive aspects of the animals, inferred by the lower percentage of pregnancy and reduced offspring quantity. Although we did not observe teratogenic effect, we observed that the accumulation of PS NPs in embryos was significantly correlated with a redox unbalance, without, however, having a cholinesterasic effect (via evaluation of AChE and BChE activity) in embryos. Thus, by evidencing the accumulation of PS NPs in embryos of P. reticulata females exposed to the pollutant during the gestational period, we confirm not only the plausibility of the maternal transfer of these nanomaterials, but also their consequent physiological impacts on the offspring, which has not yet been demonstrated in live-bearing freshwater fish.